A method for preparing a high temperature resistant rubber composite material

By adding aminodiphenylacetylene phenolic resin and epoxy soybean oil to natural rubber and carrying out high-temperature chemical crosslinking reaction, the problems of poor high temperature resistance and flame retardant properties of traditional natural rubber materials are solved, and better mechanical properties and flame retardant effects are achieved.

CN119039679BActive Publication Date: 2025-04-08DONGGUAN CHANGHAO PLASTIC PROD CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411346977.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-04-08
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Traditional natural rubber materials have problems with poor high temperature resistance and flame retardant properties.

Method used

By adding aminodiphenylacetylene phenolic resin and epoxy soybean oil to the natural rubber, and performing chemical crosslinking reactions at high temperatures, a tight chemical crosslinking structure is formed to improve the interfacial compatibility and mechanical properties of the material.

Benefits of technology

The high temperature resistance and flame retardant properties of rubber composites are significantly improved, and their tensile strength and elongation at break are enhanced, while reducing the peak combustion heat release rate and the total heat release amount.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005061238080000021
    Figure BDA0005061238080000021
  • Figure BDA0005061238080000031
    Figure BDA0005061238080000031
  • Figure BDA0005061238080000091
    Figure BDA0005061238080000091
Patent Text Reader

Abstract

The invention relates to the technical field of natural rubber, and discloses a method for preparing a high-temperature resistant rubber composite material. The high-temperature resistant rubber composite material comprises epoxidized natural rubber, aminophenyl phenolic resin, epoxy soybean oil, ammonium polyphosphate, zinc oxide, stearic acid, an antioxidant, an accelerator, and sulfur. During high-temperature mixing, the active amino group of the phenolic resin can react with the epoxy group of the epoxidized natural rubber and the epoxy soybean oil, which is beneficial to the tensile strength, elongation at break and mechanical properties of the rubber composite material. The aminophenyl phenolic resin contains the heat-resistant structure of phenyl acetylene, and the phenolic resin also has the characteristics of good heat resistance and high carbonization, which improves the mass loss temperature and residual carbon content of the material, reduces the peak value of the combustion heat release rate and the total heat release, and makes the natural rubber composite material have better high-temperature resistance and flame retardant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of natural rubber, in particular to a method for preparing a high-temperature resistant rubber composite material. Background Art

[0002] Natural rubber is the most widely used general-purpose rubber. The main component is cis-1,4-polyisoprene. It has good resilience, insulation, water resistance, alkali resistance and other properties, and is widely used in tires, gloves, catheters, mattresses, etc. Natural rubber contains unsaturated olefin bonds, which can generate epoxy groups after oxidation, which can improve the reactivity of natural rubber and its own physical and chemical properties. Traditional natural rubber has poor mechanical properties, poor high temperature resistance, and easy burning. Therefore, reinforcing natural rubber and improving its comprehensive performance is a research hotspot.

[0003] Adding inorganic fillers, nanomaterials, polymer resins and other materials to natural rubber can enhance the mechanical properties of natural rubber. Phenolic resin has good mechanical properties, heat resistance and flame retardancy, can be used as a carbonizing agent, and is widely used in plastics, rubber and other materials. The invention patent with announcement number CN105670048B discloses that the modified natural rubber bridge bearing material obtained by using CPE rubber and natural rubber as the rubber matrix and terpene phenolic resin as an auxiliary agent has good physical and mechanical properties, as well as wear resistance, ozone resistance, aging resistance and other properties. However, the patent does not solve the problem of poor high temperature resistance and flame retardancy of natural rubber materials. Summary of the invention

[0004] The invention solves the problem that the rubber material has poor high temperature resistance and flame retardancy.

[0005] Technical solution: A method for preparing a high temperature resistant rubber composite material:

[0006] Step A, add phenolic resin to toluene, stir, then dropwise add a toluene solution containing 4'-nitrotoluene-4-carbonyl chloride and triethylamine, react in a nitrogen atmosphere, pour the solution into a separatory funnel, add water, extract and separate, distill the organic phase under reduced pressure, and dry to obtain nitrotoluene phenolic resin.

[0007] Step B, add nitrotoluene phenolic resin, hydrazine hydrate solution, palladium carbon catalyst to ethanol, filter and collect the catalyst after the reaction, distill the filtrate under reduced pressure, wash with water, and dry to obtain aminotoluene phenolic resin. The reaction route is:

[0008]

[0009] Step C, adding epoxidized natural rubber, aminodiphenylethynyl phenolic resin and epoxidized soybean oil into a torque rheometer, mixing at 140-150°C for 10-20 minutes, then adding ammonium polyphosphate, zinc oxide, stearic acid and an antioxidant, mixing for 5-8 minutes, placing the materials in a double-roll open mill after debonding, adding an accelerator and sulfur, performing thin pass, and sheeting; finally, vulcanizing the materials in a flat vulcanizer at 140-155°C for 10-30 minutes to obtain a high temperature resistant rubber composite material.

[0010] Furthermore, in step A, the masses of 4'-nitrotoluene-4-carbonyl chloride and triethylamine are 20-60% and 7-22% of the mass of the phenolic resin, respectively.

[0011] Furthermore, in step A, the reaction is carried out at 20-45° C. for 12-24 h.

[0012] Furthermore, in step B, the mass of the hydrazine hydrate solution and the palladium-carbon catalyst is 26-80% and 0.28-0.85% of the mass of the nitrotoluene phenolic resin.

[0013] Further, in step B, the reaction is condensed and refluxed at 75-80° C. for 4-6 h.

[0014] Furthermore, in step C, the mass of the aminodiphenylethynyl phenolic resin and the epoxidized soybean oil are 10-30% and 3-15% of the mass of the epoxidized natural rubber, respectively.

[0015] Further, the preparation method of 4'-nitrophenylacetylene-4-carbonyl chloride comprises: adding 4-iodobenzoic acid, 4-nitrophenylacetylene, bis(triphenylphosphine)palladium dichloride, triethylamine, and cuprous iodide to toluene, and performing a coupling reaction in a nitrogen atmosphere. After filtering, the solution is poured into a separatory funnel, water is added, and extraction and separation are performed. The organic phase is dried over anhydrous sodium sulfate, and the filtrate is concentrated under reduced pressure after filtering. The product is recrystallized from dichloromethane, and finally added to thionyl chloride for chlorination reaction, and concentrated under reduced pressure to remove thionyl chloride to obtain 4'-nitrophenylacetylene-4-carbonyl chloride. The reaction formula is:

[0016]

[0017] Furthermore, the molar ratio of 4-iodobenzoic acid, 4-nitrophenylacetylene, bis(triphenylphosphine)palladium dichloride, triethylamine, and cuprous iodide is 1:(1.2-1.3):(0.01-0.012):(10-15):(0.018-0.024).

[0018] Further, the coupling reaction is carried out at 70-80°C for 4-8h; and the acyl chlorination reaction is carried out at 60-70°C for 2-3h.

[0019] Technical effect: The present invention utilizes the acyl chloride group of 4'-nitrotolan-4-carbonyl chloride to react with the hydroxyl group of phenolic resin, and then reduces the nitro group to obtain aminotolan phenolic resin.

[0020] The present invention uses aminobenzene phenolic resin and epoxy soybean oil to modify epoxidized natural rubber. During high-temperature mixing, the active amino groups of the phenolic resin can react with the epoxy groups of the epoxidized natural rubber and the epoxy soybean oil, so that the three form a tight chemical cross-linking structure, which can improve the interface compatibility between the three. The phenolic resin itself has high mechanical strength, and the epoxy soybean oil has a flexible alkyl long chain, thereby playing a good toughening and improving elongation at break effect. It is beneficial to the tensile strength, elongation at break and mechanical properties of the rubber composite material.

[0021] The aminotoluene acetylene phenolic resin of the present invention contains the heat-resistant structure of toluene, and the acetylene group can undergo crosslinking and cyclization reaction at high temperature to form an aromatic condensed ring structure with thermal stability and high carbonization. The phenolic resin also has the characteristics of good heat resistance and high carbonization, and forms a chemical crosslinking effect with the epoxidized natural rubber, which limits the movement of the rubber molecular chain and is conducive to improving the thermal decomposition temperature and heat resistance. At the same time, when burning, the acetylene phenolic resin forms a continuous carbon layer structure in the natural rubber material, which has the flame retardant effects of heat insulation and oxygen isolation, improves the mass loss temperature and residual carbon content of the material, reduces the peak value of the combustion heat release rate and the total heat release, and makes the natural rubber composite material have better high temperature resistance and flame retardant properties. DETAILED DESCRIPTION

[0022] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0023] Epoxidized natural rubber ENR25, Zhonghe Chemical (Shandong) Co., Ltd. Phenolic resin, model 2123, Jinan Dahui Chemical Technology Co., Ltd. Palladium carbon catalyst, item number: gffxc152, brand: Guangfu, Tianjin Guangfu Technology Development Co., Ltd.

[0024] Example 1

[0025] (1) 6 mmol 4-iodobenzoic acid, 7.2 mmol 4-nitrobenzeneacetylene, 0.072 mmol bis(triphenylphosphine)palladium dichloride, 90 mmol triethylamine, and 0.108 mmol cuprous iodide were added to 20 mL toluene, and a coupling reaction was carried out at 70°C for 8 h in a nitrogen atmosphere. After filtering, the solution was poured into a separatory funnel, water was added, and extraction and separation were performed. The organic phase was dried over anhydrous sodium sulfate, and the filtrate was concentrated under reduced pressure after filtering. The product was recrystallized from dichloromethane and finally added to 8 mL thionyl chloride. The chlorination reaction was carried out at 70°C for 2 h, and the thionyl chloride was removed by concentration under reduced pressure to obtain 4'-nitrotoluene-4-carbonyl chloride.

[0026] (2) Add 8 g of phenolic resin to 30 mL of toluene, stir, and then dropwise add 8 mL of a toluene solution containing 2.9 g of 4'-nitrotoluene-4-carbonyl chloride and 1.32 g of triethylamine. Stir and react at 30° C. in a nitrogen atmosphere for 24 h. Pour the solution into a separatory funnel, add water, extract and separate, and distill the organic phase under reduced pressure and dry to obtain nitrotoluene phenolic resin.

[0027] (3) Add 10 g of nitrophenyl phenolic resin, 6.3 g of hydrazine hydrate solution (mass fraction 80%), and 0.058 g of palladium carbon catalyst to 150 mL of ethanol, and reflux the mixture at 75° C. for 6 h. Collect the catalyst by filtration, and distill the filtrate under reduced pressure, wash with water, and dry to obtain aminophenyl phenolic resin.

[0028] (4) 200 g of epoxidized natural rubber, 20 g of aminodiphenylethynyl phenolic resin, and 6 g of epoxidized soybean oil were added to a torque rheometer and kneaded at 140° C. for 20 min. Then, 22 g of ammonium polyphosphate, 15 g of zinc oxide, 3.2 g of stearic acid, and 2.3 g of antioxidant 4010 were added and kneaded for 5 min. After debonding, the material was placed in a double-roll mill, 2 g of accelerator CZ and 4.2 g of sulfur were added, and thin-passed and sheeted. Finally, the material was vulcanized in a flat vulcanizer at 145° C. for 30 min to obtain a high-temperature resistant rubber composite material.

[0029] Example 2

[0030] (1) Add 6 mmol 4-iodobenzoic acid, 7.8 mmol 4-nitrobenzeneacetylene, 0.06 mmol bis(triphenylphosphine)palladium dichloride, 60 mmol triethylamine, and 0.144 mmol cuprous iodide to 25 mL toluene, and carry out coupling reaction at 80°C for 4 h in a nitrogen atmosphere. After filtering, pour the solution into a separatory funnel, add water, and extract and separate. The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is concentrated under reduced pressure. The product is recrystallized from dichloromethane and finally added to 8 mL thionyl chloride. Carry out chlorination reaction at 60°C for 3 h, and then concentrate under reduced pressure to remove thionyl chloride to obtain 4'-nitrotoluene-4-carbonyl chloride.

[0031] (2) Add 8 g of phenolic resin to 25 mL of toluene, stir, and then dropwise add 5 mL of a toluene solution containing 1.2 g of 4'-nitrotoluene-4-carbonyl chloride and 0.56 g of triethylamine. Stir and react at 20° C. in a nitrogen atmosphere for 24 h. Pour the solution into a separatory funnel, add water, extract and separate, and distill the organic phase under reduced pressure and dry to obtain nitrotoluene phenolic resin.

[0032] (3) Add 10 g of nitrophenyl phenolic resin, 2.6 g of hydrazine hydrate solution (mass fraction 80%), and 0.028 g of palladium carbon catalyst to 120 mL of ethanol, and condense and reflux the mixture at 75° C. for 4 h. Collect the catalyst by filtration, and distill the filtrate under reduced pressure, wash with water, and dry to obtain aminophenyl phenolic resin.

[0033] (4) 200 g of epoxidized natural rubber, 35 g of aminodiphenylethynyl phenolic resin, and 14 g of epoxidized soybean oil were added to a torque rheometer and mixed at 145° C. for 20 min. Then, 25 g of ammonium polyphosphate, 10 g of zinc oxide, 4.6 g of stearic acid, and 2 g of antioxidant 4010 were added and mixed for 5 min. After debonding, the material was placed in a double-roll mill, 2.2 g of accelerator CZ and 5 g of sulfur were added, and thin-passed and sheeted. Finally, the material was vulcanized in a flat vulcanizer at 140° C. for 30 min to obtain a high-temperature resistant rubber composite material.

[0034] Example 3

[0035] (1) 8 g of phenolic resin was added to 30 mL of toluene. After stirring, 10 mL of a toluene solution containing 3.6 g of 4'-nitrotoluene-4-carbonyl chloride (prepared in the same manner as in Example 1) and 0.56 g of triethylamine was added dropwise. The mixture was stirred at 45° C. for 12 h in a nitrogen atmosphere. The solution was poured into a separating funnel, water was added, and the mixture was separated by extraction. The organic phase was distilled under reduced pressure and dried to obtain nitrotoluene phenolic resin.

[0036] (2) Add 10 g of nitrophenyl phenolic resin, 8 g of hydrazine hydrate solution (mass fraction 80%), and 0.085 g of palladium carbon catalyst to 180 mL of ethanol, and condense and reflux the mixture at 80° C. for 6 h. Collect the catalyst by filtration, and distill the filtrate under reduced pressure, wash with water, and dry to obtain aminophenyl phenolic resin.

[0037] (3) 200 g of epoxidized natural rubber, 45 g of aminodiphenylethynyl phenolic resin, and 22 g of epoxidized soybean oil were added to a torque rheometer and kneaded at 150° C. for 10 min. Then, 27 g of ammonium polyphosphate, 18 g of zinc oxide, 4 g of stearic acid, and 1.8 g of antioxidant 4010 were added and kneaded for 8 min. After debonding, the material was placed in a double-roll mill, 2.6 g of accelerator CZ and 4 g of sulfur were added, and thin-passed and sheeted. Finally, the material was vulcanized in a flat vulcanizer at 155° C. for 10 min to obtain a high-temperature resistant rubber composite material.

[0038] Example 4

[0039] (1) 8 g of phenolic resin was added to 30 mL of toluene, and after stirring, 8 mL of a toluene solution containing 2 g of 4'-nitrotoluene-4-carbonyl chloride (prepared in the same manner as in Example 1) and 0.94 g of triethylamine was added dropwise. The mixture was stirred at 20° C. in a nitrogen atmosphere for 24 h. The solution was poured into a separating funnel, water was added, and the mixture was separated by extraction. The organic phase was distilled under reduced pressure and dried to obtain nitrotoluene phenolic resin.

[0040] (2) Add 10 g of nitrophenyl phenolic resin, 4.3 g of hydrazine hydrate solution (mass fraction 80%), and 0.046 g of palladium carbon catalyst to 180 mL of ethanol, and reflux the mixture at 75° C. for 6 h. Collect the catalyst by filtration, and distill the filtrate under reduced pressure, wash with water, and dry to obtain aminophenyl phenolic resin.

[0041] (3) 200 g of epoxidized natural rubber, 60 g of aminodiphenylethynyl phenolic resin, and 30 g of epoxidized soybean oil were added to a torque rheometer and kneaded at 150° C. for 15 min. Then, 30 g of ammonium polyphosphate, 10 g of zinc oxide, 3.2 g of stearic acid, and 2.3 g of antioxidant 4010 were added and kneaded for 8 min. After debonding, the material was placed in a double-roll mill, 2 g of accelerator CZ and 5 g of sulfur were added, and thin-passed and sheeted. Finally, the material was vulcanized in a flat vulcanizer at 140° C. for 20 min to obtain a high-temperature resistant rubber composite material.

[0042] Comparative Example 1

[0043] The difference between this comparative example and Example 1 is that aminodiphenylethynyl phenolic resin and epoxy soybean oil are not added.

[0044] (1) 200 g of epoxidized natural rubber, 22 g of ammonium polyphosphate, 15 g of zinc oxide, 3.2 g of stearic acid, and 2.3 g of antioxidant 4010 were added to a torque rheometer and mixed at 140°C for 5 min. After debinding, the material was placed in a double-roll mill, 2 g of accelerator CZ and 4.2 g of sulfur were added, and thin-passed and sheeted. Finally, the material was vulcanized in a flat vulcanizer at 145°C for 30 min to obtain a high-temperature resistant rubber composite material.

[0045] Comparative Example 2

[0046] The difference between this comparative example and Example 1 is that no epoxidized soybean oil is added.

[0047] (1) 200 g of epoxidized natural rubber and 20 g of aminophenyl phenolic resin were added to a torque rheometer and kneaded at 140° C. for 20 min. Then, 22 g of ammonium polyphosphate, 15 g of zinc oxide, 3.2 g of stearic acid, and 2.3 g of antioxidant 4010 were added and kneaded for 5 min. After the rubber was discharged, the material was placed in a double-roll mill, 2 g of accelerator CZ and 4.2 g of sulfur were added, and thin-passed and rolled. Finally, the material was vulcanized in a flat vulcanizer at 145° C. for 30 min to obtain a high-temperature resistant rubber composite material.

[0048] Comparative Example 3

[0049] The difference between this comparative example and Example 1 is that aminobenzaline phenol-formaldehyde resin is not added.

[0050] (1) 200 g of epoxidized natural rubber and 6 g of epoxidized soybean oil were added to a torque rheometer and kneaded at 140°C for 20 min. Then, 22 g of ammonium polyphosphate, 15 g of zinc oxide, 3.2 g of stearic acid, and 2.3 g of antioxidant 4010 were added and kneaded for 5 min. After debonding, the material was placed in a double-roll mill, 2 g of accelerator CZ and 4.2 g of sulfur were added, and thin-passed and sheeted. Finally, the material was vulcanized in a flat vulcanizer at 145°C for 30 min to obtain a high-temperature resistant rubber composite material.

[0051] Comparative Example 4

[0052] The difference between this comparative example and Example 1 is that phenolic resin is used instead of aminobenzaline phenolic resin.

[0053] (1) 200 g of epoxidized natural rubber, 20 g of phenolic resin, and 6 g of epoxidized soybean oil were added to a torque rheometer and kneaded at 140° C. for 20 min. Then, 22 g of ammonium polyphosphate, 15 g of zinc oxide, 3.2 g of stearic acid, and 2.3 g of antioxidant 4010 were added and kneaded for 5 min. After debonding, the material was placed in a double-roll mill, 2 g of accelerator CZ and 4.2 g of sulfur were added, and thin-passed and sheeted. Finally, the material was vulcanized in a flat vulcanizer at 145° C. for 30 min to obtain a high-temperature resistant rubber composite material.

[0054] Comparative Example 5

[0055] The difference between this comparative example and Example 1 is that nitrotolan phenolic resin is used instead of aminotolan phenolic resin.

[0056] (1) 200 g of epoxidized natural rubber, 20 g of nitrophenyl phenolic resin, and 6 g of epoxidized soybean oil were added to a torque rheometer and mixed at 140° C. for 20 min. Then, 22 g of ammonium polyphosphate, 15 g of zinc oxide, 3.2 g of stearic acid, and 2.3 g of antioxidant 4010 were added and mixed for 5 min. After debonding, the material was placed in a double-roll mill, 2 g of accelerator CZ and 4.2 g of sulfur were added, and thin-passed and sheeted. Finally, the material was vulcanized in a flat vulcanizer at 145° C. for 30 min to obtain a high-temperature resistant rubber composite material.

[0057] The tensile properties of rubber composites were tested according to GB / T 528-2009 method.

[0058] 4 mg of the rubber composite material was weighed and placed in a thermogravimetric analyzer for thermal performance testing in a nitrogen atmosphere with a heating rate of 10°C / min and a test temperature of 20-800°C.

[0059] The combustion properties of rubber composites were tested using a cone calorimeter with a sample size of 80 mm × 80 mm × 5 mm. The thermal radiation intensity was 50 kW / m 2 .

[0060] Table 1 Properties of rubber composites

[0061]

[0062] T 5% is the temperature at which 5% mass loss occurs. PHRR is the peak heat release rate of combustion. THR is the total heat release.

[0063] As shown in Table 1, compared with Comparative Example 1, the tensile properties, T 5%, the residual carbon content is significantly increased, PHRR and THR are significantly reduced, showing good mechanical properties, high temperature resistance and flame retardant properties. This is mainly because the phenolic resin itself has a very high mechanical strength, and the epoxy soybean oil has a flexible alkyl long chain, which can play a role in toughening and improving the elongation at break. In addition, the aminodiphenylethynyl phenolic resin contains active amino groups, which can react with the epoxy groups of epoxidized natural rubber and epoxy soybean oil during high-temperature mixing, so that the three form a tight chemical cross-linking structure, which can improve the interfacial compatibility between the three, so that the phenolic resin and epoxy soybean oil play a good role in strengthening and toughening, which is beneficial to improve the tensile strength and elongation at break.

[0064] In addition, the aminodiphenylacetylene phenolic resin contains the heat-resistant structure of diphenylacetylene. The acetylene group can undergo cross-linking and cyclization reactions at high temperatures to form an aromatic condensed ring structure with thermal stability and high carbon-forming property. The phenolic resin also has the characteristics of good heat resistance and high carbon-forming property. It forms a chemical cross-linking effect with the epoxidized natural rubber, which limits the movement of the rubber molecular chain and is beneficial to improving the thermal decomposition temperature and heat resistance. At the same time, when burning, the acetylene phenolic resin forms a continuous carbon layer structure in the natural rubber material, which has flame retardant effects such as heat insulation and oxygen isolation, increases the mass loss temperature and residual carbon content, reduces PHRR and THR, and makes the natural rubber composite material have better high temperature resistance and flame retardant properties.

[0065] Comparative Example 2 did not add epoxidized soybean oil, and the elongation at break of the composite material was lower, but the mass loss temperature and residual carbon content were significantly higher than those of Comparative Example 1, and the PHRR and THR were lower than those of Comparative Example 1, and the high temperature resistance and flame retardancy were very good.

[0066] Comparative Example 3 did not add aminodiphenylethynyl phenolic resin, and its high temperature resistance and flame retardancy were poor. Although epoxy soybean oil was added, its elongation at break was slightly lower than that of Example 1. This may be because the epoxy soybean oil could not react with the epoxidized natural rubber, and the two had poor compatibility and poor toughening effect.

[0067] Comparative Example 4 uses phenolic resin instead of aminodiphenylethynyl phenolic resin. It does not contain active amino groups, and is difficult to react with epoxidized natural rubber and epoxidized soybean oil. The compatibility between the three is poor, and the strengthening and toughening effects are not good. In addition, the phenolic resin does not contain diphenylethynyl structure, resulting in the composite material having a mass loss temperature and a carbon residue lower than that of Comparative Example 1, and PHRR and THR higher than that of Comparative Example 1, and poor high temperature resistance and flame retardancy.

[0068] Comparative Example 5 uses nitrotolan phenolic resin instead of aminotolan phenolic resin. It does not contain active amino groups and is difficult to react with epoxidized natural rubber and epoxidized soybean oil. The compatibility between the three is poor, and the strengthening and toughening effects are not good. In addition, the high temperature resistance and flame retardancy are lower than those of Example 1. However, the composite material contains a tolan structure, and the mass loss temperature and residual carbon content are higher than those of Comparative Example 4, and the PHRR and THR are lower than those of Comparative Example 4.

[0069] Although the specific embodiments of the present invention are described above, those skilled in the art should understand that the specific test groups described are only illustrative and not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a high temperature resistant rubber composite material, characterized in that: The preparation method comprises: Step A, adding phenolic resin to toluene, adding dropwise a toluene solution containing 4'-nitrotoluene-4-carbonyl chloride and triethylamine after stirring, reacting in a nitrogen atmosphere, extracting and separating, distilling the organic phase under reduced pressure, and drying to obtain nitrotoluene phenolic resin; Step B, adding nitrotolan phenolic resin, hydrazine hydrate solution, and palladium-carbon catalyst to ethanol, filtering after the reaction, distilling the filtrate under reduced pressure, washing, and drying to obtain aminotolan phenolic resin; Step C, adding epoxidized natural rubber, aminodiphenylethynyl phenolic resin and epoxidized soybean oil into a torque rheometer, mixing at 140-150°C for 10-20 minutes, then adding ammonium polyphosphate, zinc oxide, stearic acid and an antioxidant, mixing for 5-8 minutes, placing the materials in a double-roll open mill after debonding, adding an accelerator and sulfur, performing thin pass, and sheeting; finally, vulcanizing the materials in a flat vulcanizer at 140-155°C for 10-30 minutes to obtain a high temperature resistant rubber composite material.

2. The method for preparing a high temperature resistant rubber composite material according to claim 1, characterized in that: In the step A, the masses of 4'-nitrotolane-4-carbonyl chloride and triethylamine are 20-60% and 7-22% of the mass of the phenolic resin, respectively.

3. The method for preparing a high temperature resistant rubber composite material according to claim 1, characterized in that: In the step A, the reaction is carried out at 20-45° C. for 12-24 h.

4. The method for preparing the high temperature resistant rubber composite material according to claim 1, characterized in that: In the step B, the mass of the hydrazine hydrate solution and the palladium-carbon catalyst is 26-80% and 0.28-0.85% of the mass of the nitrotolanthin phenolic resin.

5. The method for preparing a high temperature resistant rubber composite material according to claim 1, characterized in that: In the step B, the reaction is condensed and refluxed at 75-80° C. for 4-6 hours.

6. The method for preparing a high temperature resistant rubber composite material according to claim 1, characterized in that: In the step C, the mass of the aminodiphenylethynyl phenolic resin and the epoxidized soybean oil are 10-30% and 3-15% of the mass of the epoxidized natural rubber respectively.

7. The method for preparing a high temperature resistant rubber composite material according to claim 2, characterized in that: The preparation method of 4'-nitrophenylacetylene-4-carbonyl chloride comprises: adding 4-iodobenzoic acid, 4-nitrophenylacetylene, bis(triphenylphosphine)palladium dichloride, triethylamine and cuprous iodide into toluene, carrying out coupling reaction in a nitrogen atmosphere, extracting and separating, drying the organic phase, concentrating the filtrate under reduced pressure after filtering, recrystallizing, and finally adding the filtrate into thionyl chloride to carry out chlorination reaction, and concentrating under reduced pressure to obtain 4'-nitrophenylacetylene-4-carbonyl chloride.

8. The method for preparing the high temperature resistant rubber composite material according to claim 7, characterized in that: The molar ratio of the 4-iodobenzoic acid, 4-nitrobenzeneacetylene, bis(triphenylphosphine)palladium dichloride, triethylamine and cuprous iodide is 1:(1.2-1.3):(0.01-0.012):(10-15):(0.018-0.024).

9. The method for preparing a high temperature resistant rubber composite material according to claim 7, characterized in that: The coupling reaction is carried out at 70-80°C for 4-8 hours; the acyl chlorination reaction is carried out at 60-70°C for 2-3 hours.

Citation Information

Patent Citations

  • A kind of modified natural rubber bridge support material and preparation method thereof

    CN105670048B

  • Modified phenolic resin applicable to RTM (resin transfer moulding) as well as preparation method and application of resin

    CN104086727A

  • M-acetylenyl benzeneazo biphenyl phenolic resin and preparation method thereof

    CN104558533A